2015
DOI: 10.1080/14680629.2015.1029678
|View full text |Cite
|
Sign up to set email alerts
|

New method to estimate the “re-activated” binder amount in recycled hot-mix asphalt

Abstract: The magnitude of the binder re-activation within the reclaimed asphalt pavement (RAP) fraction is a major concern when recycled hot-mix asphalt (HMA) is produced, since it directly affects the final performance of the mix. Currently, no reliable methods to predict the RAP binder re-activation are available and the lack of such information prevents the quantification of the proper amount of virgin binder to be added to the recycled HMA.This study proposes a new method to estimate the re-activated binder amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The quantity of RA binder in the asphalt mix is identified sometime as asphalt binder replacement, recycled binder ratio, effective RAP binder, RAP binder contribution, RAP binder activity, RAP working binder, RAP binder availability (Kaseer, Arámbula-Mercado, & Martin, 2019), replaced virgin binder (Davide Lo Presti, Jimenez del Barco Carrion, Airey, & Hajj, 2016) and amount of re-activated binder (Stimilli, Virgili, & Canestrari, 2015). In mix design practices, this quantity is considered as a percentage of RA binder by weight with respect to the total binder by weight in the asphalt mixture, however its accurate estimation still raises concerns due to its ultimate effect on mxi performance.…”
Section: State Of the Art: Degree Of Blending And Related Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…The quantity of RA binder in the asphalt mix is identified sometime as asphalt binder replacement, recycled binder ratio, effective RAP binder, RAP binder contribution, RAP binder activity, RAP working binder, RAP binder availability (Kaseer, Arámbula-Mercado, & Martin, 2019), replaced virgin binder (Davide Lo Presti, Jimenez del Barco Carrion, Airey, & Hajj, 2016) and amount of re-activated binder (Stimilli, Virgili, & Canestrari, 2015). In mix design practices, this quantity is considered as a percentage of RA binder by weight with respect to the total binder by weight in the asphalt mixture, however its accurate estimation still raises concerns due to its ultimate effect on mxi performance.…”
Section: State Of the Art: Degree Of Blending And Related Factorsmentioning
confidence: 99%
“…Several studies showed that if the RA content is too high, more energy would be required to activate the RA binder (Booshehrian et al, 2013;Gottumukkala et al, 2018;Huang, Pauli, Grimes, & Turner, 2014;Kriz et al, 2014;McDaniel, Soleymani, Anderson, Turner, & Peterson, 2000;Oliver, 2001;Shirodkar et al, 2011;Stimilli et al, 2015;Zhang et al, 2015;Zhao et al, 2015).…”
Section: Content Of Ra In a New Mixturementioning
confidence: 99%
See 2 more Smart Citations
“…The activation of the RAP binder is necessary for its mixing and blending with the virgin binder and virgin aggregate. The degree of binder activation also determines the homogeneity of the asphalt mixture with RAP [ 25 ]. Currently, there are no reliable testing methods to predict the RAP binder activation degree.…”
Section: Introductionmentioning
confidence: 99%